(untitled) (Environment & Health, 2021)
Objective: We determined a role of folate metabolism genotypes in the occurrence of hyperhomocysteinemia in children after a forest fire in the Chоrnobyl exclusion zone (ChEZ). Material and methods: In the study, we applied immunochemical, Real-time PCR, mathematical and statistical methods. Results: A survey of 84 adolescents from the Poliske district, Kiev region revealed changes in their metabolic processes in the form of increased homocysteine production in connection with a forest fire in the ChEZ which was recorded during April 26-29, 2015. A comparative analysis of the specific gravity of the folate cycle genotypes in the subgroups of the children with hyperhomocysteinemia before and after a forest fire showed that an endogenous factor in the form of a genetic apparatus, controling synthesis of folate cycle enzymes, was not involved in this phenomenon. Сonclusions: Forest and peat fires in the Chernobyl exclusion zone are one of the main causes for the elevation in blood homocysteine levels in children from the adjacent districts, regardless of the state of folate metabolism genetic system. Monitoring of the blood homocysteine levels in children and adults living under conditions of the exposure to wood combustion gases, containing radioactive elements, is a key component of the programmer for the prevention of cancer and cardiovascular diseases.